2018
DOI: 10.1111/php.12990
|View full text |Cite
|
Sign up to set email alerts
|

Heteropogon contortusBL‐1 (Pilli Grass) and Elevated UV‐B Radiation: The Role of Growth, Physiological, and Biochemical Traits in Determining Forage Productivity and Quality

Abstract: Exposure to elevated UV-B (eUV-B) is well known for its phytotoxicity, although studies made with UV-B exposure and its impact on grasses are limited especially from tropical countries including India. In this study, responses of a valuable grass species, Heteropogon contortus BL-1, were assessed under eUV-B (over ambient UV-B) at different growth stages. Damage caused by eUV-B was observed in the form of membrane damage and loss of pigments at early stages of growth, whereas tannin, phenol, and protein conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Singh et al (2008) also found shorter plants with reduced leaf area in Vigna unguiculata due to eUV-B treatments. Similarly, the retardation was also reported in Heteropogon contortus (Hamid et al 2019); Phaseolus vulgaris (Singh et al 2014), Fagopyrum esculentum (Regvar et al 2012) and Abelmoschus esculentus (Kumari et al 2009b) under UV-B stress. Reduction in plant growth was probably not only due to the destruction of endogenous IAA concentration on the shoot tips by UV-B induced photodegradation but may also be due to alternation in transport of auxin and excessive oxidative stress resulted in a decline in overall plant stature and photosynthesis (Takshak and Agrawal 2018).…”
Section: Discussionmentioning
confidence: 57%
“…Singh et al (2008) also found shorter plants with reduced leaf area in Vigna unguiculata due to eUV-B treatments. Similarly, the retardation was also reported in Heteropogon contortus (Hamid et al 2019); Phaseolus vulgaris (Singh et al 2014), Fagopyrum esculentum (Regvar et al 2012) and Abelmoschus esculentus (Kumari et al 2009b) under UV-B stress. Reduction in plant growth was probably not only due to the destruction of endogenous IAA concentration on the shoot tips by UV-B induced photodegradation but may also be due to alternation in transport of auxin and excessive oxidative stress resulted in a decline in overall plant stature and photosynthesis (Takshak and Agrawal 2018).…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have assessed the effects of elevated UV‐B on crop plants, but data are limited for non‐crop plants (Sullivan et al , 1992). Hamid et al (2018) are the only group to assess the response of an Indian grass ( Heteropogon sp.) to UV‐B.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated UV‐B exerts several structural, biochemical and physiological effects on plants (Bancroft et al , 2007). High doses of UV‐B can lead to damaged membranes from accumulation of reactive oxygen species (ROS) ( Choudhary & Agrawal, 2014a,b; Hamid et al , 2018). To alleviate UV‐B stress, plants synthesize secondary metabolites, mainly phenolics, flavonoids and hydroxycinnamate esters, which accumulate in vacuoles of epidermal cells and can attenuate penetration of UV‐B into deeper photosynthetic tissues (Frohnmeyer & Staiger, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations